Learning to Comprehend Foreign‐Accented Speech by Means of Production and Listening Training. (September 2016) - Grohe, Ann‐Kathrin; Weber, Andrea
Abstract : The effects of production and listening training on the subsequent comprehension of foreign‐accented speech were investigated in a training‐test paradigm. During training, German nonnative (L2) and English native (L1) participants listened to a story spoken by a German speaker who replaced all English /θ/s with /t/ (e.g., * teft for theft ) or they produced the story themselves with the t‐substitutes. During test, participants made auditory lexical decisions to English words with t‐substitutes. L2 participants' reaction times to words from the training were significantly faster after having produced the story than after no training; having listened to the short story also resulted in faster reaction times, but less strongly so. For L1 participants, the facilitatory effect of training did not differ significantly between production and listening training. Thus, only for L2 participants, the effect of accent production for adaptation was superior to accent listening.